THE RELATIONSHIP BETWEEN DIVIDEND PAYOUT AND FIRM PERFORMANCE: A STUDY OF LISTED COMPANIES IN KENYA - Timothy Mahalang’ang’a Murekefu; Ochuodho Peter Ouma (European Scientific Journal, ESJ, 2012)
Several theories have been documented on the relevance and irrelevance of dividend policy. Many authors continue to come up with different findings from their studies on the relevance of dividend policy. This research sought to establish the relationship between dividend payout and firm performance among listed firms in the Nairobi Securities Exchange. Regression analysis was carried out to establish the relationship between dividend payout and firm performance. The findings indicated that dividend payout was a major factor affecting firm performance. Their relationship was also strong and positive. This therefore showed that dividend policy was relevant. It can be concluded, based on the findings of this research that dividend policy is relevant and that managers should devote adequate time in designing a dividend policy that will enhance firm performance and therefore shareholder value.